Purification and Structured Term in Ation of Compounds in Chloroform Extract of the Aerial Parts of the Plant Ferula hirtella - Z Habibi; E Roustaei (Institue of Medicinal Plants, ACECR, 2013)
Background: Ferula is a genus of about 130 species of flowering plants in the family Umbelliferae, of which 30 species are found in Iran. Many species of this family possess medicinal qualities and have long been used in traditional medicine. Objective: This research aims to isolate, separate and determine the structure of the compounds found in the chloroform extract of the aerial parts of Ferula hirtella. Methods:We collect F. hirtella form the site of its natural habitat in Ābāde, Fars Province. The chloroform extract of the aerial parts is derived and then mixture separation using Column chromatography is performed. Results: Using Column chromatography purification methods, we were able to separate, for the first time, two coumarins, Farneciferol C and Umbelliprenin, and a steroid compound, β-stigmasterol from the chloroform extract of the F. hirtella which were identified using C NMR and H NMR spectral data. Conclusion: A majority of the compounds found in the chloroform extract of the aerial parts of F. hirtella are coumarins. Separation of β-stigmasterol from the chloroform extract of this genus was achieved for the first time.